A 4‐year follow‐up case of extrusive luxation in a patient with cerebral palsy. (3rd January 2019) - Véliz Ramírez, Andrea; Krämer Strenger, Susanne; Solar López, Melissa; Muñoz Cortes, Pamela; Corral Núñez, Camila
Abstract: Cerebral palsy (CP) is a condition caused by brain damage before, during, or shortly after birth. Communication can be a challenge when treating patients with CP. Some patients can communicate verbally, while others use augmentative alternative communication tools or have individualized means of communication. Therefore, professional dental treatment in individuals with CP is challenging, especially if the patient is affected by dental trauma and requires emergency treatment. This report shows how individualized communication skills assessment allowed us to successfully manage a 9‐year‐old patient with CP, who suffered extrusive luxation of the permanent lower incisor. In the present case, the teeth were repositioned briefly after the trauma had occurred and then stabilized with a flexible splint according to international guidelines. The teeth remained vital and periodontal repair was observed during the 4‐year follow‐up.